An Interview with Maine PUC Chairman Kenneth Gordon - Staff, Editorial (Maine Policy Review, 1991)
In August, 1991, Maine Policy Review interviewed Kenneth Gordon, the current chair of the Maine Public Utilities Commission. That interview centered on important public policy issues that surround the regulation of telecommunications in Maine and the U.S. From his experience as an economist with the Federal Communications Commission, Gordon brings to his current position an extensive background in telecommunications. Since that interview, he has been elected president of the National Association of Regulatory Utility Commissioners, so his views on telecommunications are likely to have significance in national, as well as state, policy.